Овощные культуры на приусадебном участке - Ганичкина Октябрина Алексеевна (Знание, 1988)
Экземпляры: КХ (20101207) / Инвентарный номер: 933293 / Цена: 0.25 / Сис.шифр: 42.34 / Авт.знак: Г 19 / ГРНТИ: 68 / ББК: 42.340